Electrophoretic mobility of magnetically labeled yeast cells S. cerevisiae - Karpenko, Y.V.; Gorobets, S.V. (Functional Materials, 2012)
Research of ζ-potential of cell wall of magnetically labeled yeast cells was proposed by measuring electrophoretic mobility to determine the nature and mechanisms of cell wall interaction with environment. The results showed that biosorption of copper cations (II) and attaching the magnetic beads clearly reduce the electrophoretic mobility of cells and thus the interaction with functional groups distributed on the cell surface takes place in these processes.